2021
DOI: 10.1159/000517951
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes after Early Neonatal Hyperglycemia in VLBW Infants: A Systematic Review

Abstract: <b><i>Introduction:</i></b> Long-term effects of early hyperglycemia in VLBW infants are poorly characterized. The objective of this study was to systematically review the effect of early hyperglycemia on growth, metabolic health, and neurodevelopment after neonatal intensive care unit discharge in VLBW infants. <b><i>Methods:</i></b> The systematic review was conducted in accordance with the PRISMA guidelines. A study protocol was registered in PROSPERO (CRD4201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
(142 reference statements)
1
14
0
Order By: Relevance
“…Our findings agree with other recent reviews on the subject [ 35 , 36 ]: while hyperglycemia negatively impacts short-term clinical outcomes in preterm infants [ 15 ], more uncertainties remain about the impact of hyperglycemia on long-term outcomes. The variable definition of a glucose threshold for hyperglycemia in this population contributes to conclusions drawn on this topic.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings agree with other recent reviews on the subject [ 35 , 36 ]: while hyperglycemia negatively impacts short-term clinical outcomes in preterm infants [ 15 ], more uncertainties remain about the impact of hyperglycemia on long-term outcomes. The variable definition of a glucose threshold for hyperglycemia in this population contributes to conclusions drawn on this topic.…”
Section: Discussionsupporting
confidence: 93%
“…The variable definition of a glucose threshold for hyperglycemia in this population contributes to conclusions drawn on this topic. Paulsen et al [ 36 ] underlined the critical need for well-designed studies that could provide stronger evidence on this topic. Unlike Paulsen et al [ 36 ], we focused only on neurological outcome, and we used stricter criteria, excluding studies without a control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Beardsall et al (25) revealed that although early elective insulin therapy reduces hyperglycemia, it dramatically raises the risk of hypoglycemia and mortality by the first 28 days of life, raising doubts about its effectiveness in the prevention and treatment of hyperglycemia in premature infants. More recently, the long-term effects of early hyperglycemia in VLBW infants did not yield reliable advice for how to address the condition (26) .…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have demonstrated the risks associated with hyperglycemia, insulin treatment has not been associated with clear benefits [14]. Little is known about the long-term consequences of hyperglycemia in surviving VPT infants, although available data indicate an increased risk for adverse outcomes [15, 16]. Furthermore, since most studies have focused on extremely low birth weight or extremely preterm (EPT) infants, i.e., with a gestational age (GA) <28 weeks, less is known about potential effects of hyperglycemia in more mature VPT infants (GA <28–31 weeks).…”
Section: Introductionmentioning
confidence: 99%